Strategi Komunikasi Pemasaran Digital Kartu By.U - Wahyu Sugiarto; Wulan Tri Gartanti (Bandung Conference Series: Public Relations, 2022)
Abstract. The digital era is currently developing, one of which is in the field of communication. The demand for the internet continues to increase, even every year there is always a rapid increase. Currently, many providers are present in Indonesia by offering various advantages such as the digital provider by.U. by. U is the first digital provider in Indonesia where the target is the millennial generation or Gen Z. This is what makes researchers interested in researching more deeply about by. U. This study uses marketing communication theory by Soemanegara, to find out the description of marketing communication in increasing sales. The researcher uses a qualitative method with a case study approach. To obtain relevant data, the subjects in this study were employees of the company by. U. with data collection techniques in the form of interviews and observations which then the data will be analyzed through three stages, namely, data reduction, data presentation, and drawing conclusions. The results of this study indicate that By.U manages its marketing communications by doing social media marketing, influencer marketing, and digital placement so that customers want to buy the products offered by the company. by. U uses a digital marketing strategy because By.u itself is the first digital provider in Indonesia and also because it follows the development of an increasingly modern era. The Marketing Communication Strategy in this study consists of social media marketing, influencer marketing, and digital placement. Abstrak. Era digital saat ini sedang berkembang salah satunya dibidang komunikasi. Permintaan akan internet terus meningkat bahkan tiap tahun selalu mengalami peningkatan yang pesat saat ini banyak provider hadir di Indonesia dengan menawarkan berbagai keunggulannya seperti provider digital by.U. by. U merupakan provider digital pertama di Indonesia dimana targetnya merupakan generasi milenial atau Gen Z. Hal tersebut yang membuat peneliti tertarik untuk meneliti lebih dalam mengenai by. U. Penelitian ini menggunakan teori komunikasi pemasran oleh Soemanegara, untuk mengetahui gambaran komunikasi pemasaran dalam meningkatkan penjualan. Peneliti menggunakan metode kualitatif dengan pendekatan studi kasus. Untuk mendapatkan data yang relavan maka subjek dalam penelitian ini adalah karyawan perusahaan by. U. dengan teknik pengambilan data berupa wawancara dan observasi yang kemudia data tersebut akan dianalisis melalui tiga tahap yaitu, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa By.U mengelola komunikasi pemasarannya dengan melakukan sosial media marketing, influencer marketing, dan digital placement agar pelanggan mau membeli produk yang ditawarkan perusahaan. By. U menggunakan strategi pemasaran digital karena By.u sendiri merupakan provider digital pertama di Indonesia dan juga krena mengikuti perkembangan zaman yang semakin modern. Strategi Komunikasi Pemasaran dalam penelitian ini terdiri dari sosial media marketing, influencer marketing, dan digital placement.